2018
DOI: 10.1002/gps.4856
|View full text |Cite
|
Sign up to set email alerts
|

Associations between CSF cortisol and CSF norepinephrine in cognitively normal controls and patients with amnestic MCI and AD dementia

Abstract: Enhanced responsiveness of the HPA axis to noradrenergic stimulatory regulation in AD and disruption of the blood brain barrier may contribute to these findings. Because brainstem noradrenergic stimulatory regulation of the HPA axis is substantially increased by both acute and chronic stress, these findings are also consistent with AD participants experiencing higher levels of acute and chronic stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 39 publications
0
24
0
Order By: Relevance
“…There is evidence from experimental studies that cortisol might exacerbate Aβ and tau pathology in the brain, while mifepristone, a glucocorticoid antagonist, can decrease cerebral Aβ and tau load in a mouse model of AD ( Ouanes and Popp, 2019 ). In human subjects, one study from the Alzheimer’s Disease Neuroimaging Initiative (ADNI) found CSF cortisol levels to be positively correlated with CSF tau and p-tau, but not CSF Aβ 1–42 ( Wang et al, 2018 ). Findings of studies that measured cortisol levels in the serum have been contradictory ( Laske et al, 2009 ; Pena-Bautista et al, 2019 ), possibly due to methodological differences and to the relationship between cortisol, Aβ and tau changing as the disease progresses.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence from experimental studies that cortisol might exacerbate Aβ and tau pathology in the brain, while mifepristone, a glucocorticoid antagonist, can decrease cerebral Aβ and tau load in a mouse model of AD ( Ouanes and Popp, 2019 ). In human subjects, one study from the Alzheimer’s Disease Neuroimaging Initiative (ADNI) found CSF cortisol levels to be positively correlated with CSF tau and p-tau, but not CSF Aβ 1–42 ( Wang et al, 2018 ). Findings of studies that measured cortisol levels in the serum have been contradictory ( Laske et al, 2009 ; Pena-Bautista et al, 2019 ), possibly due to methodological differences and to the relationship between cortisol, Aβ and tau changing as the disease progresses.…”
Section: Discussionmentioning
confidence: 99%
“…Carroll et al (2011) [81] have observed that the prolonged stress caused by this hyperactivation also causes an increase in the accumulation of hyperphosphorylated tau and neurodegeneration in mice. In humans, increased levels of cortisol were observed in patients with AD compared to the control group [8284]. Huang et al (2009) [85] observed in a 2-year follow-up of patients with AD that the higher cortisol levels correlated with the faster progression of the disease, worsened in the MMSE and smaller volume of the hippocampus region when observed by resonance.…”
Section: Acquired Risk Factorsmentioning
confidence: 99%
“…Given that altered cortisol secretion plays a role in the etiology of many diseases marked by cognitive impairments [e.g., Addison's disease, Cushing's syndrome, Alzheimer's disease, major depressive disorder, post-traumatic stress disorder, and metabolic syndrome; (130,181,185,(198)(199)(200)(201)(202)], and given the known alterations in cortisol concentrations in patients with AD on replacement therapy, it is important to determine the physiological mechanisms by which chronically altered circadian rhythms impact cognitive functioning. One such mechanism may be through sleep, given that a bidirectional relationship exists between circadian rhythmicity and the sleep-wake cycle, and because successful memory consolidation of information learned during the day is known to rely on sleep (1,90,203).…”
Section: Variations In Cortisol Concentrations and Their Effects On Cognitionmentioning
confidence: 99%